2020
DOI: 10.1101/2020.03.10.20033795
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Active or latent tuberculosis increases susceptibility to COVID-19 and disease severity

Abstract: medRxiv preprint SARS-CoV-2 infection. Patients with active or latent TB were more susceptible to SARS-CoV-2, and COVID-19 symptom development and progression were more rapid and severe.Meaning: Tuberculosis status should be assessed carefully at patient admission and management and therapeutic strategies adjusted accordingly to prevent rapid development of severe COVID-19 complications. AbstractImportance: Risk factors associated with COVID-19, the viral pneumonia originating in Wuhan, China, in Dec 2019, req… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
157
1
11

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 167 publications
(171 citation statements)
references
References 8 publications
2
157
1
11
Order By: Relevance
“…Each article that met selection criteria was fundamentally assessed for Author/Country, Population/Study design, Exposures, Comparators, Treatments, TB occurrence and SARS/MERS/COVID-19 severity, recovery and mortality rate. [28][29][30][31], one case control study [32] and four case series [33][34][35][36] were conducted in China, two case series [37][38] were done in Singapore, one case series [39] and one case control study [40] were undertaken in Saudi Arabia, a case series [41] was conducted in Italy, one cohort study was done in South Africa [42] and another in the Philippines [43], one case study was conducted in the United State of America [44], other three case studies were found in Turkey [45], Hong Kong [46] and India [47] respectively.…”
Section: Search Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Each article that met selection criteria was fundamentally assessed for Author/Country, Population/Study design, Exposures, Comparators, Treatments, TB occurrence and SARS/MERS/COVID-19 severity, recovery and mortality rate. [28][29][30][31], one case control study [32] and four case series [33][34][35][36] were conducted in China, two case series [37][38] were done in Singapore, one case series [39] and one case control study [40] were undertaken in Saudi Arabia, a case series [41] was conducted in Italy, one cohort study was done in South Africa [42] and another in the Philippines [43], one case study was conducted in the United State of America [44], other three case studies were found in Turkey [45], Hong Kong [46] and India [47] respectively.…”
Section: Search Resultsmentioning
confidence: 99%
“…However, the mortality rates for COVID-19/TB or COVID/HIV/TB coinfection seem to be higher than the mortality rate of 3.81% for COVID-19 worldwide [7]. Three studies [32,[40][41] reported COVID-19 recovery time from 9 to 54 days. This is important to highlight that qualitative analysis included three cases related to SARS-CoV/HIV/TB co-infection (one case) [46] and COVID-19/HIV/TB co-infection (two cases) [27][28][29][30][31][32][33][34][35][36][37][38][39][40][41].…”
Section: Descriptive Analysismentioning
confidence: 99%
See 2 more Smart Citations
“…The recent COVID-19 pandemic has forced researchers to focus on the different aspects of this disease, and studying factors that can predispose the individual to disease (20). Studies have investigated the effect of nutrition (21), serum parameters, such as blood group (22) and elevated plasmin(ogen) (23), as well as underlying autoimmune diseases, such as tuberculosis (24) and lupus erythematosus (25), on COVID-19 susceptibility. However, as far as the authors are concerned, the risk of COVID-19 infection in women with endometriosis has not been clinically evaluated, to date.…”
Section: Discussionmentioning
confidence: 99%